Synthesis of Phidianidines A and B - Lin, Hong-Yu (2012)
Reaction of a substituted indole-3-acetyl chloride with N-5-azidopentyl-N′-hydroxyguanidine generated a substituted 3-(5-azidopentylamino)-5-((indol-3-yl)-methyl)-1,2,4-oxadiazole. Reduction of the azide with zinc and ammonium formate afforded the amine, which was elaborated to the guanidine, completing short and efficient syntheses of the cytotoxic natural products phidianidines A and B in 19% overall yield by a convergent route that will make analogues readily available for biological evaluation. Initial screening in the NCI 60 cell line at 10(−5) M indicated that the bromine on the indole is necessary for activity and that the amine precursor to phidianidine A is more potent than phidianidine A.